The Effect of the SAVI Learning Model on Arabic Writing Skills: A Case Study at MTS Arrukhsatul ‘Ulum, West Bandung - Mohammad Sabarudin; Ibnu Imam Al Ayyubi; Irfan Suryana; Rifqi Rohmatulloh; Saepulloh Saepulloh (LPPM STAIS Dharma Indramayu, 2023)
Arabic language education in schools intends to improve students' ability to communicate globally and understand in both oral and written aspects. Language skills consist of four aspects namely, listening, speaking, reading, and writing skills. This research was conducted at MTs Arrukhshatul 'Ulum West Bandung with quantitative research. This research method uses a survey method with correlation analysis to see the relationship between the independent variable, namely student learning independence, and the dependent variable, namely student learning outcomes, using the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model on Arabic writing material. This study aims to evaluate and measure the impact and how much significant influence is produced by the use of the SAVI learning model on the Arabic writing skills of 8th grade students at MTs Arrukhshatul 'Ulum West Bandung. This study has a very strong relationship between learning independence and student learning outcomes, or, in other words, student learning independence has a very strong effect on student learning outcomes, with a correlation coefficient value of 0.914. In addition, learning independence has an influence of 83.4% on student learning outcomes and the other 16.6% is influenced by factors outside student learning independence with the regression equation model Y = 19.012 + 0.727X